Nematomorpha from Hong Kong and description of a new species from Malaysia - Schmidt-Rhaesa, Andreas; Karraker, Nancy E. (Zootaxa, 2017)
We report here for the first time horsehair worms (Nematomorpha) from Hong Kong (China). Most specimens belong to the genus Chordodes, and can be assigned to C. bipilus, C. caledoniensis and to C. cf. moutoni. Two specimens have a cuticular pattern resembling the South American species C. peraccae or C. bouvieri, but for Southeast Asia this pattern is new. These two specimens are reported here as Chordodes sp. Additionally, Gordionus chinensis was found. One new species, Acutogordius koljai, is described from Malaysia. It has a characteristically-structured region posterior to the postcloacal crescent which sets it apart from previously described species in this genus.